Analysing the effect of thermal modification on the calorific values of Eucalyptus nitens wood - Nepal, Saurav (Les (Ljubljana), 2021)
Gross and net calorific value of 13 samples of Eucalyptus nitens wood were determined at HAWK (Hochschule für Angewandte Wissenschaft und Kunst), Göttingen, Germany. Among 13 samples, 12 were thermally modified and one was unmodified. Calorific values of samples were determined by using a bomb calorimeter, and the wood components (cellulose, hemicellulose, lignin, and extractives) already analysed by Wentzel et al. (2019). After determination of the values, samples were statistically analysed by R studio to find the relations among the calorific value, temperature, and wood components. The gross calorific value and net calorific value of the untreated sample of Eucalyptus nitens were found to be 18.83 MJ/kg and 17.48 MJ/kg, and after thermal modification these increased up to 20.24 MJ/kg and 18.84 MJ/kg. Upon statistical analysis, the results for lignin showed a strong correlation with the temperature of thermal treatment and calorific value
Keywords: cellulose, hemicellulose; celuloza; ekstrativi; Eucalyptus nitens; extractives; gross calorific valu; hemiceluloza; les; lignin; net calorific value; spodnja kalorična vrednost; termična modifikacija; thermal modification; zgornja kalorična vrednost,